The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1142/s0219519414400132
|View full text |Cite
|
Sign up to set email alerts
|

Balloon-Expandable Stents Expansion in Tapered Vessels and Their Interactions

Abstract: In-stent restenosis (ISR) after stent implantation, especially in tapered vessels, remains an obstacle in the long-term benefits of stenting. In the present study, a finite element method (FEM) was employed to investigate the expansion process of balloon-expandable stents in tapered vessels (the TV model) and their interactions. For comparison, a numerical model of the same stent deployment in a straight vessel was also investigated. Results showed that in the TV model, the peak tissue stresses took place at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 15 publications
2
5
0
Order By: Relevance
“…This may be caused by the fact that, for a given stent design and expansion strategy, the larger the tapering level of the vessel, the higher the reaction force, especially at the distal end of the stent, which accordingly increased the risk of stent fracture. This was in accordance with the results of Shen et al 24 The obtained results suggested that the geometry of the patient's vessel may be an important factor for the clinician to choose the stent. The stent which more closely conforms to the vessel may greatly reduce the probability of failure and prolong the service time of the stent in vivo.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This may be caused by the fact that, for a given stent design and expansion strategy, the larger the tapering level of the vessel, the higher the reaction force, especially at the distal end of the stent, which accordingly increased the risk of stent fracture. This was in accordance with the results of Shen et al 24 The obtained results suggested that the geometry of the patient's vessel may be an important factor for the clinician to choose the stent. The stent which more closely conforms to the vessel may greatly reduce the probability of failure and prolong the service time of the stent in vivo.…”
Section: Discussionsupporting
confidence: 92%
“…However, the ratio of the vessel thickness to the lumen radius was 0.43 (t/r i = 0.43). 23,24 Detailed data of tapered vessels and tapered plaques were listed in Tables 1 and 2, respectively.…”
Section: Geometric Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the straight vessel, the stent implantation in the tapered vessel with the same stent length resulted in greater vessel and plaque stress, and the Von Mises stress of the plaque-artery system gradually increased from its proximal end to its distal end during stent expansion. The result showed good agreement with the findings of the numerical simulation study (Shen et al 2014). The result also indicated an increased stent recoil and a decreased stent foreshortening after the stent implantation in the tapered vessel.…”
Section: Discussionsupporting
confidence: 86%
“…It is widely accepted that finite element analysis (FEA) is a powerful tool for computational modeling, revealing the structural response of the arterial walls during stent implantation (Eshghi et al 2011;Imani et al 2013a;Imani 2013). The factors that influence stent implantation involve the stent loading method (Imani et al 2014), the stent structural design (Hara et al 2006;Lally et al 2005;Hsiao et al 2012;Imani et al 2013bImani et al , 2015, the wire stent fabrication technique (Zhao et al 2012a), the material of the stent (Schiavone et al 2014), and the plaque and vessel geometry (Dottori et al 2016;Shen et al 2014;Wei et al 2016). A few researchers have used FEA to study the effect of these factors on stent and vascular mechanical properties (Gu et al 2010;Hyre and Pulliam 2008;Cui et al 2010;Zhao et al 2012b).…”
Section: Introductionmentioning
confidence: 99%